Hukum Meriwayatkan dan Mengamalkan Hadis Daif untuk Fadhail al-A'mal - Yusram, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2017)
This study explains the matter of â€œThe Ruling and Acting on Weak Hadits of Fadhail al Aâ€™malâ€. Hadits is undeniable to be one source of the Islamic Syariâ€™ah law and legality, but not all is attributed as the sayingss of the Prophet Mohamed (PBUH). The scholars of Hadits had agreed on the acceptance of the sound (Sahih) Hadits and good (Hasan) Hadits as the guidance in rulings and law determination. However, there are differences among them in terms of weak (Daâ€™if) hadits, primarily that concerns with Fadhail Aâ€™maal. The scholars have 3 different perspectives on it; some scholars prohibit, some permit and the rests of them permit it with certain strict conditions. The first argument is adopted by most of the scholars of Hadits and it appears as the strongest arguments with regard to its accuracy so as to prevent ones from falsehood in the name of The Prophet Mohamed (PBUH). Moreover, the conditions of its permission referred by a group of scholars seems difficult to implement. The existence of Sound (Sahih) Hadits and Hasan (Good) Hadits also suffices the Moslem needs as guidance in their various life aspects.